Bacterial and Archaeal Viruses of Himalayan Hot Springs at Manikaran Modulate Host Genomes - Sharma, Anukriti; Schmidt, Matthias; Kiesel, Bärbel; Mahato, Nitish K.; Cralle, Lauren; Singh, Yogendra; Richnow, Hans H.; Gilbert, Jack A.; Arnold, Wyatt; Lal, Rup (Frontiers in Microbiology, 2018)
Hot spring-associated viruses, particularly the archaeal viruses, remain under-examined compared to bacteriophages. Previous metagenomic studies of the Manikaran hot springs in India suggested an abundance of viral DNA, which prompted us to examine the virus-host (bacterial and archaeal) interactions in sediment and microbial mat samples collected from the thermal discharges. Here, we characterize the viruses (both bacterial and archaeal) from this Himalayan hot spring using both metagenomics assembly and electron microscopy. We utilized four shotgun samples from sediment (78-98°C) and two from microbial mats (50°C) to reconstruct 65 bacteriophage genomes (24-200kb). We also identified 59 archaeal viruses that were notably abundant across the sediment samples. Whole-genome analyses of the reconstructed bacteriophage genomes revealed greater genomic conservation in sediments (65%) compared to microbial mats (49%). However, a minimal phage genome was still maintained across both sediment and microbial mats suggesting a common origin. To complement the metagenomic data, scanning-electron and helium-ion microscopy were used to reveal diverse morphotypes of Caudovirales and archaeal viruses. The genome level annotations provide further evidence for gene-level exchanges between virus and host in these hot springs, and augments our knowledgebase for bacteriophages, archaeal viruses and Clustered Regularly Interspaced Short Palindromic Repeat cassettes, which provide a critical resource for studying viromes in extreme natural environments.